Amelioration of Sensory Nerve Dysfunction by C-Peptide in Patients With Type 1 Diabetes - Ekberg, Karin; Brismar, Tom; Johansson, Bo-Lennart; Jonsson, Björn; Lindström, Per; Wahren, John (Diabetes (New York, N.Y.), 2003)
Amelioration of Sensory Nerve Dysfunction by C-Peptide in Patients With Type 1 Diabetes Karin Ekberg 1 , Tom Brismar 2 , Bo-Lennart Johansson 1 , Björn Jonsson 1 , Per Lindström 3 and John Wahren 1 1 Department of Surgical Sciences, Section of Clinical Physiology, Department of Clinical Neuroscience, Karolinska Institutet, Stockholm, Sweden 2 Section of Clinical Neurophysiology, Karolinska Institutet, Stockholm, Sweden 3 Section of Neurology, Karolinska Institutet, Stockholm, Sweden Abstract Studies have demonstrated that proinsulin C-peptide stimulates the activities of Na + ,K + -ATPase and endothelial nitric oxide synthase, both of which are enzyme systems of importance for nerve function and known to be deficient in type 1 diabetes. The aim of this randomized double-blind placebo-controlled study was to investigate whether C-peptide replacement improves nerve function in patients with type 1 diabetes. Forty-nine patients without symptoms of peripheral neuropathy were randomized to either 3 months of treatment with C-peptide (600 nmol/24 h, four doses s.c.) or placebo. Forty-six patients (15 women and 31 men, aged 29 years, diabetes duration 10 years, and HbA 1c 7.0%) completed the study. Neurological and neurophysiological measurements were performed before and after 6 and 12 weeks of treatment. At baseline the patients showed reduced nerve conduction velocities in the sural nerve (sensory nerve conduction velocity [SCV]: 50.9 ± 0.70 vs. 54.2 ± 1.2 m/s, P < 0.05) and peroneal nerve (motor nerve conduction velocity: 45.7 ± 0.55 vs. 53.5 ± 1.1 m/s, P < 0.001) compared with age-, height-, and sex-matched control subjects. In the C-peptide treated group there was a significant improvement in SCV amounting to 2.7 ± 0.85 m/s ( P < 0.05 compared with placebo) after 3 months of treatment, representing 80% correction of the initial reduction in SCV. The change in SCV was accompanied by an improvement in vibration perception in the patients receiving C-peptide ( P < 0.05 compared with placebo), whereas no significant change was detectable in cold or heat perception. In conclusion, C-peptide administered for 3 months as replacement therapy to patients with early signs of diabetic neuropathy ameliorates nerve dysfunction. Footnotes Address correspondence and reprint requests to John Wahren, MD, Karolinska Institutet, Department of Surgical Sciences, Section of Clinical Physiology, Karolinska Hospital N1:05, SE-171 76 Stockholm, Sweden. E-mail: john.wahrenatks.se . Received for publication 27 August 2002 and accepted in revised form 11 November 2002. ARI, aldose reductase inhibitor; CMAP, compound muscle action potential; eNOS, endothelial nitric oxide synthase; MCV, motor nerve conduction velocity; SCV, sensory nerve conduction velocity; SNAP, sensory nerve action potential amplitude; STZ, streptozotocin DIABETES